PENDEKATAN DAN TANTANGAN DALAM MANAJEMEN PENDIDIKAN ISLAM - Lilis Suryani; Neng Vika Zuliani (Jurnal Salome : Multidisipliner Keilmuan, 2026)
Islamic education has become a crucial focus in developing the potential of students in accordance with the demands of Law Number 20 of 2003 concerning the National Education System in Indonesia. This article discusses the understanding, approaches, and challenges in the management of Islamic education. The concept of Islamic education management encompasses resource management to achieve educational goals effectively and efficiently. Approaches in this management include contextual, scientific, philosophical, and religious, each playing a significant role in developing Islamic education. However, there are significant challenges to be faced, such as unresponsive curriculum innovation and teaching methods, as well as decentralization and autonomy in education that require adaptation by Islamic educational institutions. The management of Islamic education is expected to respond to the demands of the times and maintain its identity and excellence in educating future generations.